Analisis Kekuatan Mekanik Komposit Polimer Diperkuat Serbuk Kulit Kerang - Zulfikar, Achmad Jusuf; Ritonga, Din Aswan A.; Pranoto, Siswo; Nasution, Fadly A. Kurniawan; Arif, Zainal; Junaidi, Junaidi (Rekayasa Material, Manufaktur dan Energi, 2023)
In recent decades, the development of composite material technology has continued to increase rapidly and has been used for various applications as an alternative material to replace metal. In line with growing environmental issues, the utilization of natural materials which are abundant in nature and easy to find is the main priority for composite building materials. In this study, shell powder was used as a reinforcing material for epoxy polymer composites. The aims of this study were to obtain the average compressive, tensile, and flexural strength of shell powder-reinforced polymer composite materials, to calculate the distribution of test results using the PDF method, and to calculate the contribution of shell powder to the mechanical properties mentioned using the ANOVA method. The tensile, compressive, and flexural test specimens follow the test specimen standards of ASTM D638, ASTM D7264, and ASTM D695 respectively. The composition of shell powder consists of 10%, 30%, and 50%. Testing of these mechanical properties using a UTM-type hydraulic test equipment model WEW-300D with a capacity of 300 kN. The test results show an increase in the mechanical properties of the material. The increase occurred in compressive and flexural strength where the composition was given up to 30% and 50%, namely between 120 – 125 MPa. However, increasing the composition of shell powder at 30% and 50% actually resulted in a decrease in tensile strength between 12 – 9 MPa. Finally, based on the results of ANOVA analysis, it was shown that the addition of shell powder as a reinforcement for polymer composites significantly improved their mechanical properties.